Audit of Psychosocial and Palliative Care Support for Children Having Allogeneic Stem Cell Transplants at the New Zealand National Allogeneic Transplant Centre - Amanda M. Evans; Hiran Thabrew; Bruce Arroll; Nyree Cole; Ross Drake (Children, 2021)
Psychosocial and palliative care support during stem cell transplants (SCT) is known to improve outcomes. Aim: evaluate the support provided to children and families at the New Zealand National Allogeneic Stem Cell Transplant unit (NATC). Method: the psychosocial and palliative care support for children who received SCT between December 2012 and April 2018 was audited. Results: of the 101 children who received SCT, 97% were reviewed by the social work team (SW) and 82% by the psychiatric consult liaison team (CLT) at least once during their illness. However, pre-transplant psychological assessment only occurred in 16%, and during the SCT admission, only 55% received SW support, and 67% received CLT support. Eight out of eighty-five families (9%) were offered support for siblings. Eight of the sixteen children who died were referred for pediatric palliative care (PPC) with all supported and half the families who experienced a death (n = 8; 50%) received bereavement follow up. Conclusion: although the majority received some social work and psychological support, auditing against the standards suggests the consistency of involvement could be improved. Referrals for PPC were inadequate and largely for end-of-life phase. Sibling support, in particular donor siblings, had insufficient psychological assessment and support. Key recommendations are provided to address this underperformance.